Analisa Fitokimia dan Aktivitas Antioksidan Sirup Poliherbal yang Mengandung Daun Kelor, Rimpang Kunyit, dan Rimpang Jahe: Phytochemical Analysis and Antioxidant Activity of Polyherbal Syrup Containing Moringa Leaf, Turmeric, and Ginger Rhizoma - Nurmalia Zakaria; Fauziah Fauziah; Rinaldi Rinaldi; Yuni Dewi Safrida; Erliana Winingsih (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Polyherbal syrup containing Moringa leaves, turmeric rhizome and ginger rhizome (SPKKJ) is believed empirically by the people of Banda Aceh, Aceh, Indonesia, to be able to maintain health and increase body immunity. These indications are caused by antioxidant phytochemical compounds. The combination of the three in the form of syrup is one of the dosage forms with the oral route, that has the fastest absorption time and is easy to use. This study aims to analyze the phytochemical compounds and antioxidant activity of SPKKJ by DPPH scavenging. This research is an experimental quantitative study where the IC50 value of syrup preparation will be calculated based on the percent inhibition of DPPH scavening. The variables that played a role in this study were moringa leaf syrup (S1), turmeric rhizome syrup (S2), ginger rhizome syrup (S3), and SPKKJ (S4). A comparison was used as a positive control in the form of Vitamin C. The results showed that SPKKJ contained saponins, tannins, and alkaloids. IC50 of SPKKJ is 0.21 g/mL which is a very strong antioxidant. The IC50 value of SPKKJ was higher than S1, S2, S3 and Vitamin C, with a significant difference to Vitamin C (p